Integrating STEM and SDGs in Elementary School: Fostering Environmental Awareness Through Practical Chemistry - Krida Puji Rahayu; Moch Bayu Ibrahim S; Aisha Sami (Universitas Negeri Semarang, 2026)
This study examines the integration of Science, Technology, Engineering, and Mathematics (STEM) with the Sustainable Development Goals (SDGs) in elementary science learning, particularly within environmental chemistry contexts. In response to escalating global environmental challenges, elementary education plays a strategic role in fostering students’ environmental awareness and sustainable behavior from an early age. This research employs a systematic literature review (SLR) approach to analyze recent national and international studies published between 2020 and 2025 that investigate STEM-based learning aligned with SDGs. The selected studies include various hands-on and contextual learning activities, such as plastic waste recycling into paving blocks, composting organic waste, and the use of STEM-based digital learning materials. The results reveal that contextualizing chemistry concepts, including polymer properties, biodegradation, and waste management, through practical STEM projects significantly enhances students’ scientific literacy, critical thinking skills, and environmental care character. In addition, the integration of SDGs, particularly Goal 4 (Quality Education), Goal 12 (Responsible Consumption and Production), and Goal 13 (Climate Action), into elementary science curricula effectively promotes responsible environmental stewardship. These findings indicate that context-based and project-oriented STEM learning provides meaningful learning experiences that bridge scientific concepts with real-world environmental issues. This study concludes that the integration of STEM and SDGs through hands-on, contextual learning represents an effective pedagogical approach for strengthening environmental awareness in elementary education. Furthermore, this research contributes to the field of science education by offering a systematic synthesis of empirical evidence and proposing an integrated STEM–SDGs framework as a theoretically grounded model for enhancing scientific literacy and socio-environmental responsibility at the primary education level.